SINONIM DALAM MEDAN MAKNA ‘MENYAKITI’ DALAM BAHASA SASAK DIALEK NGENO-NGENE - Nisawtul Hasanah (Center of Language and Cultural Studies, 2017)
This study is aimed to describe synonyms of the word “to hurt” in context of Sasak language of Ngeno-ngene dialect. The study used ethnolinguistics approach, assigning native speakers of Sasak language that spoke Ngeno-ngene dialect residing in Mamben Lauk, Wanasaba. Data were collected using observation, interviews and document analysis. The study revealed that vocabulary items of Sasak language using Ngeno-ngene dialect were indigenous, no reference in Bahasa Indonesia appeared in this context. This potential can give contribution to deepen variety of diction in Bahasa Indonesia.